2016
DOI: 10.3102/0002831216653206
|View full text |Cite
|
Sign up to set email alerts
|

Easy in, Easy out

Abstract: Alternative certification programs are now commonplace in the credentialing of new teachers. We complement the growing evidence base for these teachers by exploring their turnover patterns in four waves of the nationally representative Schools and Staffing Survey (SASS). We report on descriptive evidence of growing differences in the characteristics of alternatively and traditionally certified teachers and the schools in which they teach. Controlling for factors that predict higher turnover, we find that by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 43 publications
1
55
2
3
Order By: Relevance
“…Using the 2007-2008 SASS administration data, these authors also found that alternatively certified teachers were significantly more likely to turnover as compared to traditionally certified teachers. The rate of turnover of alternatively certified teachers increased from 1999-2000 to 2007-2008 while the rate of traditionally certified teachers decreased during the same time-period (Redding & Smith, 2016). Boyd et al (2011) also found that alternatively certified teachers from both local New York state alternative certification programs and from the Teach for America (TFA) program were significantly more likely to turnover as compared to traditionally certified, "college recommended" (CR) teachers from New York university programs.…”
Section: The Teacher Workforce and Teacher Turnovermentioning
confidence: 89%
See 2 more Smart Citations
“…Using the 2007-2008 SASS administration data, these authors also found that alternatively certified teachers were significantly more likely to turnover as compared to traditionally certified teachers. The rate of turnover of alternatively certified teachers increased from 1999-2000 to 2007-2008 while the rate of traditionally certified teachers decreased during the same time-period (Redding & Smith, 2016). Boyd et al (2011) also found that alternatively certified teachers from both local New York state alternative certification programs and from the Teach for America (TFA) program were significantly more likely to turnover as compared to traditionally certified, "college recommended" (CR) teachers from New York university programs.…”
Section: The Teacher Workforce and Teacher Turnovermentioning
confidence: 89%
“…Teacher education and route to certification have also been previously shown to have a relationship to turnover. In an examination of SASS data, Redding and Smith (2016) found that the number of teachers entering teaching through alternative pathways has been steadily increasing, with teachers using these pathways making up 25% of the total teaching force by the 2011-2012 SASS administration. Using the 2007-2008 SASS administration data, these authors also found that alternatively certified teachers were significantly more likely to turnover as compared to traditionally certified teachers.…”
Section: The Teacher Workforce and Teacher Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…Finding roots in Milton Friedman, marketoriented education reformers seek to inject competition (note the business terminology) into the public sphere of public education. And, despite a growing body of research that suggests that charter schools underperform traditional public schools (Miron, Mathis, & Welner, 2015) and exacerbate segregation (Author & Lubienski, 2017;Frankenberg, 2011;Frankenberg & Lewis, 2012), and other research raising concerns over alternative certification programs like Teach For America (Brewer, 2014;Anderson, 2013aAnderson, , 2013bRedding & Smith, 2016;Scott, Trujillo, & Rivera, 2016), these reforms continue to expand. And these reforms are not conducted within a vacuum.…”
Section: Neoliberalism and Privatizationmentioning
confidence: 99%
“…Kane, Rockoff, & Staiger, 2008). Notwithstanding a possibility of differences in outcomes based on undergraduate training, what is clear is that background training in education strongly shapes the dispositions and approach to pedagogy (Lahann & Regan, 2011;Nukic, 2011) and that teachers who are alternatively certified are far more likely to have higher rates of turnover (Redding & Smith, 2016).…”
Section: Under30 Recipient Academic Backgrounds and Demographicsmentioning
confidence: 99%